The impact of language registers on Sepulana : a case of Mapulana a ga Mogane - Mawela, Mmasello Glothildah (University of Limpopo, 2010)
Refer to document
Thesis (M.A. (Translation studies and linguistics)) --University of Limpopo, 2010
Keywords: Language register; Sepulana; Shatale location; Northern Sotho; Language and dialect -- South Africa; Northern Sotho language -- South Africa; Sepulana language -- South Africa -- Limpopo Province